2019
DOI: 10.1242/jcs.234633
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of connexin 43 at MAPK, PKC or CK1 sites each distinctly alter the kinetics of epidermal wound repair

Abstract: The gap junction protein connexin 43 (Cx43) is a key player in wound healing, and inhibitors of Cx43, which speed epidermal wound healing, are currently in clinical trials. Here, we provide direct in vivo evidence that specific phosphorylation events on Cx43 change the physiological response during wound healing. Blocking phosphorylation, through mutation of serine residues in Cx43 at the protein kinase C (PKC) or casein kinase 1 (CK1) sites, significantly slowed the rate of wound closure in vivo and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
(56 reference statements)
4
15
0
Order By: Relevance
“…From a functional point of view, this may reflect the need for myofibroblasts to be coupled in response to stimuli that cause membrane potential alterations. However, myofibroblasts likely need to express a kind of Cx, such as Cx43, whose trafficking, half-life, and regulation (by phosphorylation) can be maximally modulated during differentiation to myofibroblast [84]. Corroborating this suggestion coming from electrophysiological records, here we found that myofibroblasts showed an increased expression of Cx43.…”
Section: Role Of Gjic and Cx43 In Myofibroblast Generationsupporting
confidence: 80%
“…From a functional point of view, this may reflect the need for myofibroblasts to be coupled in response to stimuli that cause membrane potential alterations. However, myofibroblasts likely need to express a kind of Cx, such as Cx43, whose trafficking, half-life, and regulation (by phosphorylation) can be maximally modulated during differentiation to myofibroblast [84]. Corroborating this suggestion coming from electrophysiological records, here we found that myofibroblasts showed an increased expression of Cx43.…”
Section: Role Of Gjic and Cx43 In Myofibroblast Generationsupporting
confidence: 80%
“…4g ). However, Cx43 is known to be phosphorylated at multiple sites by multiple signals 33 , 34 . To detect additional AREG-mediated pathways leading to Cx43 phosphorylation, we mutated the target phosphorylation sites on Cx43-GFP that correspond to the Akt, PKC, PKA, CK1, and MAPK signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Although speculative, an attractive idea is that somatic MPK-1A activity uses gap junctions to stimulate germline proliferation. In mice, ERK/MAPK phosphorylation of connexins modulates gap junction opening during epidermal wound healing ( Lastwika et al, 2019 ; Solan and Lampe, 2014 ). By analogy, MPK-1A could modulate gap junctions to allow unidentified proliferation-stimulatory small molecules entry into the germline.…”
Section: Discussionmentioning
confidence: 99%